Pengaruh Perbedaan Media Tanam terhadap Pertumbuhan dan Produksi Tanaman Pakcoy (Brassica rapa L.) Sistem Hidroponik - Dina Yuliasty Lamefa; Bangun Joko Laksono; Ratna Dewi; Sri Harimurti; Tukidi Tukidi; Padhel Padhel (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the influence of different planting media on the growth and production of pakcoy plants (Brassica rapa L.) in the hydroponic system. The research design used a Group Random Design (RAK) with five treatments and five replicates. The treatment provided was in the form of wood charcoal planting media, rockwool, sponges, cocopeat, and burnt husks. The parameters observed included plant height, leaf width, number of leaves, total fresh weight, and the production of pakcoy plants. The results of the study show that the planting medium has a real influence on all growth and production parameters. The highest plant height reaches 20.99 cm, leaves width 8.96 cm, number of leaves 11.06 leaves, total fresh weight of 165.00 g, and production yield of 991.71 g. Rockwool and cocopeat planting media have proven to be the most effective in increasing the growth and production of pakcoy plants compared to other media. The advantage of rockwool lies in the ability to retain optimal moisture and aeration, while cocopeat has a good capacity to retain water and nutrients. Thus, the selection of the right planting medium is an important factor in the success of pakcoy cultivation in the hydroponic system, and can be used as a reference for farmers in increasing the productivity of horticultural crops in a sustainable manner.